2011
DOI: 10.1136/bjsports-2011-090428
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroscopy for intra-articular pathology: a systematic review of outcomes with and without femoral osteoplasty

Abstract: Background Arthroscopy is increasingly used to improve pain and function in athletes with hip joint pathology. Surgical techniques have evolved to utilise arthroscopic femoral osteoplasty to address potential morphological contributors to pathology. Purpose Investigate pain and function outcomes following hip arthroscopy with and without femoral osteoplasty in individuals with intra-articular hip pathology. Study design Systematic review. Methods A comprehensive search strategy identifi ed studies that evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 84 publications
3
105
0
4
Order By: Relevance
“…A careful discussion should occur to weigh the risks against the benefits of im proved functional outcomes supported by current evidence. 6 The results from our series are in keeping with the complication rates reported in the literature. Sampson 2 suggested that hip arthroscopy was associated with a complication rate ranging from 1.6% to 5%.…”
Section: Discussionsupporting
confidence: 81%
“…A careful discussion should occur to weigh the risks against the benefits of im proved functional outcomes supported by current evidence. 6 The results from our series are in keeping with the complication rates reported in the literature. Sampson 2 suggested that hip arthroscopy was associated with a complication rate ranging from 1.6% to 5%.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies indicate that younger adults with chondropathy (articular cartilage disease) at hip arthroscopy have reduced patient-reported outcomes of pain and function compared to those without chondropathy (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…6 The current literature on the postoperative outcomes after hip arthroscopy shows a 10-year success rate with improvements in pain and function in recreationally active individuals and competitive athletes. [7][8][9] Despite a growing acceptance and rise in arthroscopic rates, a paucity of literature exists to investigate postoperative rehabilitation interventions. Specifically, evidence-based guidelines are limited to descriptive studies such as case reports and caseseries designs.…”
mentioning
confidence: 99%